THE EFFECT OF SOWING DATES ON THE YIELD OF WINTER WHEAT IN IRRIGATED MEADOW-SIEROZEM SOILS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article presents the fertility of irrigated meadow-sierozem soils, where the Davr variety of winter wheat was cultivated under different experimental variants, and the effect of sowing dates on its yield was determined. It was found that in irrigated meadow-sierozem soil conditions, when all agrotechnical processes are carried out on time and sowing is conducted between early September and the first ten days of October, the yield and quality of the Davr variety of winter wheat reach a high level.